1989
DOI: 10.1159/000226673
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Local Recurrence after Curative Surgery for Rectal Cancer

Abstract: The histories of 90 consecutive patients who underwent curative surgery for rectal cancer from January 1975 to December 1981 were reviewed. Twenty of 90 patients (22.2%) recurred locally. The site of the primary lesion and tumor differentiation are the most important factors influencing local recurrence. Median survival from recurrence was 3 months and no patient was alive after 15 months. No significant difference in survival was observed in patients surgically treated for recurrence compared to untreated pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
2

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 0 publications
2
13
0
2
Order By: Relevance
“…17, 18]. Tumor differentiation or grading has also been used to determine prognosis [1,5,12,17,19]. However the majority of authors agree that this method is inadequate since assessment of grade is in part subjective and can vary even when carried out by expert pathologists [2, 6.…”
mentioning
confidence: 99%
“…17, 18]. Tumor differentiation or grading has also been used to determine prognosis [1,5,12,17,19]. However the majority of authors agree that this method is inadequate since assessment of grade is in part subjective and can vary even when carried out by expert pathologists [2, 6.…”
mentioning
confidence: 99%
“…In previous reports [11, 12], a significant increase in local relapse was demonstrated when distal clearance was <2 cm. In group I cases, distal free margins ≥2 cm were significantly more frequent compared to stapled patients, but improved local control of disease was observed in the latter group.…”
Section: Discussionmentioning
confidence: 88%
“…Neverthless, the critical difference between APR and LAR consists in the amount of distal bowel and perirectal tissue which are removed [6, 9, 22]. It must be observed that although the surgical practice is uncommon, total mesorectal excision combined with a distal clearance of at least 2 cm also appears to increase the volume excised [10, 11, 12, 13, 14, 23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Local recurrence is a major problem in patients undergoing the surgical treatment of rectal carcinoma because it is frequent and always associated with a poor prognosis (11,12). Therefore, prediction of local recurrence could be extremely important for the management of rectal carcinoma and better local control could improve the quality of life after surgery.…”
Section: Discussionmentioning
confidence: 99%